2012
DOI: 10.1136/jech-2011-200487
|View full text |Cite
|
Sign up to set email alerts
|

Community mobilisation programme for female sex workers in coastal Andhra Pradesh, India: processes and their effects

Abstract: Background This paper describes the process of setting up community-based organisations (CBOs) of sex workers during the 5-year community mobilisation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…This demonstrated relationship between collectivisation, collective efficacy and the indicators of self-efficacy, and confidence gains importance given that FSWs are highly mobile and face multiple vulnerabilities associated with duration of sex work and educational background in cities like Mumbai and Thane 19. Importantly, findings from the current study underline the importance of collective efficacy as strategy to promote HIV prevention interventions, especially in challenging settings as evidenced in the Aastha project and elsewhere 22 23. These results parallel the previous research findings in Karnataka where it was shown that a higher degree of collectivisation was associated with increased knowledge and condom use by FSWs,5 and in Andhra Pradesh, where it was evident that higher degree of community mobilisation increased condom use and reduce violence 1 22…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This demonstrated relationship between collectivisation, collective efficacy and the indicators of self-efficacy, and confidence gains importance given that FSWs are highly mobile and face multiple vulnerabilities associated with duration of sex work and educational background in cities like Mumbai and Thane 19. Importantly, findings from the current study underline the importance of collective efficacy as strategy to promote HIV prevention interventions, especially in challenging settings as evidenced in the Aastha project and elsewhere 22 23. These results parallel the previous research findings in Karnataka where it was shown that a higher degree of collectivisation was associated with increased knowledge and condom use by FSWs,5 and in Andhra Pradesh, where it was evident that higher degree of community mobilisation increased condom use and reduce violence 1 22…”
Section: Discussionmentioning
confidence: 55%
“…All the researchers had a bachelor's degree in either sociology or statistics. The survey instrument commonly developed by Avahan for its sites in India1 17 22 23 was modified locally to add a few questions that are relevant to the local context. The survey instrument was then translated from English to Hindi.…”
Section: Methodsmentioning
confidence: 99%
“…At least one study from the United States has documented that engagement with community agencies serving MSM are more likely to be associated with safer sex behaviors among MSM, possibly due to the social support obtained from friendship networks and other resources of the community agencies [38]. Even though there is evidence of positive impact of collectivization on safer sex practices among female sex workers [39-42], there are hardly any studies on the effects of collectivization on safer sex practices among Indian MSM [43], which need to be explored further. Available evidence suggests that interventions involving community-building empowerment activities can lead to significant risk reduction in MSM [21,44].…”
Section: Discussionmentioning
confidence: 99%
“…It is also evident from the previous studies that structural approaches and community mobilization are an integral part of successful interventions in reducing the HIV risk vulnerability among key populations (e.g. female sex workers, men having sex with men and injecting drug users) [30,33,36,37,[50][51][52][53]. When mental health in the context of community collectivization approach among MSM is discussed, there is negligible evidence in this sphere of mental health.…”
Section: Discussionmentioning
confidence: 99%